Prevalence of the apolipoprotein E ε4 allele in amyloid β positive subjects across the spectrum of Alzheimer's disease. Issue 7 (27th March 2018) - Mattsson, Niklas; Groot, Colin; Jansen, Willemijn J.; Landau, Susan M.; Villemagne, Victor L.; Engelborghs, Sebastiaan; Mintun, Mark M.; Lleo, Alberto; Molinuevo, José Luis; Jagust, William J.; Frisoni, Giovanni B.; Ivanoiu, Adrian; et al.
Abstract: Introduction: Apolipoprotein E ( APOE ) ε4 is the major genetic risk factor for Alzheimer's disease (AD), but its prevalence is unclear because earlier studies did not require biomarker evidence of amyloid β (Aβ) pathology. Methods: We included 3451 Aβ+ subjects (853 AD‐type dementia, 1810 mild cognitive impairment, and 788 cognitively normal). Generalized estimating equation models were used to assess APOE ε4 prevalence in relation to age, sex, education, and geographical location. Results: The APOE ε4 prevalence was 66% in AD‐type dementia, 64% in mild cognitive impairment, and 51% in cognitively normal, and it decreased with advancing age in Aβ+ cognitively normal and Aβ+ mild cognitive impairment ( P  < .05) but not in Aβ+ AD dementia ( P  = .66). The prevalence was highest in Northern Europe but did not vary by sex or education. Discussion: The APOE ε4 prevalence in AD was higher than that in previous studies, which did not require presence of Aβ pathology. Furthermore, our results highlight disease heterogeneity related to age and geographical location.